CacyBP/SIP as a regulator of transcriptional responses in brain cells - Kilanczyk, Ewa (J Neurosci Res, 2014)
The Calcyclin-Binding Protein/Siah-1-Interacting Protein (CacyBP/SIP) is highly expressed in the brain and was shown to regulate the β-catenin-driven transcription in thymocytes. Therefore, it was investigated whether in brain cells CacyBP/SIP might play a role as a transcriptional regulator. In BDNF- or forskolin-stimulated rat primary cortical neurons, overexpression of CacyBP/SIP enhanced transcriptional activity of the cAMP-response element (CRE). In addition, overexpressed CacyBP/SIP enhanced BDNF-mediated activation of the Nuclear Factor of Activated T-cells (NFAT) but not the Serum Response Element (SRE). These stimulatory effects required an intact C-terminal domain of CacyBP/SIP. Moreover, in C6 rat glioma cells, the overexpressed CacyBP/SIP enhanced activation of CRE- or NFAT- following forskolin- or serum stimulation, respectively. Conversely, knockdown of endogenous CacyBP/SIP reduced activation of CRE- and NFAT but not SRE. Taken together, these results indicate that CacyBP/SIP is a novel regulator of CRE- and NFAT-driven transcription.